PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN PERILAKU 5S PADA PESERTA DIDIK SMKN2 TEMANGGUNG - Nur Alfi Muanayah (Al Ghazali, 2020)
This research is motivated by the phenomenon of education in Indonesia which now shows a variety of problems that are increasingly complex. The biggest problems experienced by schools today are deviant student behavior, decreased learning motivation, moral decline, and violations of school discipline. Teachers, especially Islamic religious teachers, have a duty and role to overcome these problems. This study discusses the role of Islamic religious teachers in instilling 5S behavior (smile, greeting, greeting, courtesy, politeness) in students of SMK Negeri 2 Temanggung. This research is a field research conducted at SMK Negeri 2 Temanggung. The subject of this research is the Islamic religion teacher. Methods of data collection in this study using the method of observation, interviews and documentation. Data validity techniques used data triangulation and informant reviews. The collected research data were analyzed using interactive analysis with steps, namely data reduction, data display and verification. Based on the analysis of the research results, the writer can conclude that the role of Islamic religious teachers in instilling 5S behavior includes: 1) as a leader, in this case the teacher becomes the foremost person in instilling 5S behavior in students. 2) the teacher as a good role model in the implementation of the student's 5S, 3) as a facilitator, namely the teacher is in charge of providing services to facilitate students in the learning process activities. 4) as a motivator, namely the teacher to motivate students to always carry out Islamic behavior, especially in implementing the 5S culture, 5) as an evaluator, namely the teacher to thoroughly evaluate the effective, cognitive, and psychomotor aspects, namely by implementing the 5S culture. The supporting factors in the cultivation of 5S behavior are 1) cooperation between teachers and students, 2) awareness and willingness in students, 3) the role of teachers in guiding student behavior, 4) the existence of policies given by the principal to improve the character of participants students, 5) a conducive environment in character building. The inhibiting factors for the cultivation of 5S behavior are: 1) the lack of awareness of the teacher in starting to greet students, 2) the background of different areas of origin of the students, 3) limited time for teacher meetings with students at school, 4) counter-productive student social environment . (Keywords: Teacher Role, 5S Culture)